Perbandingan Kriteria dan Sub Kriteria Pengembangan Komoditi Unggulan Agribisnis di Polewali Mandar - Bulkis, Bulkis; Pagala, Muh. Arman Yamin; Nurdiyah, Nurdiyah (Universitas Galuh, 2025)
Agroecological suitability, has high economic value, is in accordance with local socio-culture and has good technology and infrastructure. One of the regional approaches based on the development of regional superior commodities has a competitive advantage to produce one or several food commodities. Appropriate agroecological carrying capacity will be a major contributor to regional agricultural development. Therefore, the right regional development method is needed, the development of superior commodity-based agribusiness will have an important meaning for the preparation of regional development systems, especially Polewali Mandar Regency. The research was conducted in Polewali Mandar Regency from January to December 2024. Data collection methods were interviews, group discussions and document searches. Respondent sampling technique based on purposive sampling. Priority selection of superior commodities is carried out using the AHP method, Shift share, productivity calculations, and quantitative analysis. The results of the comparison matrix analysis of the criteria then agroecosystem considerations have an average elgen value of 0.49, indicating that this element must be considered in determining the priority scale developed. Then the second consideration is the economic aspect with an average elgen value of 0.23, human resources 0.16, socio-cultural 0.09 and carrying capacity 0.04. Analysis of alternative comparison matrix on economic, agroecosystem, socio-cultural, human resources and carrying capacity aspects of rice, cocoa, coconut and coffee commodities has the highest value. There are some commodities that need to be replaced such as the development of corn and papaya commodities. Commodity preference values based on consideration of criteria and sub-criteria, rice is the main choice with a higher commodity preference value of 0.4, coconut with a value of 0.2, cocoa 0.1, coffee 0.1, corn 0.007 and papaya 0.004..